The Blind Spot: Failure to Marry the Doctrine of Vicarious Liability with the Financial Recourse Mechanism of Officials - Asep Sapsudin; Reyraya Respati Paramudhita (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study exposes a structural blind spot in Indonesia’s constitutional and administrative law: the failure to enforce individual accountability against law enforcement officers who abuse operational discretion. It focuses on the lack of synchronization between state vicarious liability and personal financial recourse mechanisms targeting officials’ private assets. Using doctrinal legal research with statutory, conceptual, and comparative approaches, the study analyzes inconsistencies in the 1945 Constitution, Administrative Government Law, Administrative Court Law, internal ethics enforcement, and judicial precedents on factual government actions. Findings reveal a chronic procedural vacuum in executing the state’s right of recourse against officials acting with malice or gross negligence. Ambiguity in distinguishing official from personal faults has turned the state budget into a shield for individual repression, undermining institutional legitimacy and violating the social contract with taxpayers. Key obstacles include rigid procedural barriers, the failure to separate official from personal assets, and an institutional culture that conceals abuses through opaque disciplinary processes. The study proposes a procedural blueprint featuring cumulative objective–subjective lawsuits, a shifted burden of proof, conservatoire beslag (asset freezing), punitive damages, automated wage garnishment, and strict pre-trial screening to prevent frivolous or SLAPP litigation.